Computational Linguistics and Intelligent Text Processing 9th International Conference, CICLing 2008, Haifa, Israel, February 17-23, 2008, Proceedings - Gelbukh, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
CICLing 2008 (www. CICLing. org) was the 9th Annual Conference on Intel- gent Text Processing and Computational Linguistics. The CICLing conferences are intended to provide a wide-scope forum for the discussion of both the art and craft of natural language processing research and the best practices in its applications. This volume contains the papers accepted for oral presentation at the c- ference, as well as several of the best papers accepted for poster presentation. Other papers accepted for poster presentationwerepublished in specialissues of other journals(seethe informationonthe website). Since 2001the CICLing p- ceedings have been published in Springer’s Lecture Notes in Computer Science series, as volumes 2004, 2276, 2588, 2945, 3406, 3878, and 4394. The book consists of 12 sections, representative of the main tasks and app- cations of Natural Language Processing: – Language resources – Morphology and syntax – Semantics and discourse – Word sense disambiguation and named entity recognition – Anaphora and co-reference – Machine translation and parallel corpora – Natural language generation – Speech recognition – Information retrieval and question answering – Text classi?cation – Text summarization – Spell checking and authoring aid A total of 204 papers by 438 authors from 39 countries were submitted for evaluation (see Tables 1 and 2). Each submission was reviewed by at least two independent Program Committee members. This volume contains revised v- sions of 52 papers by 129 authors from 24 countries selected for inclusion in the conference program (the acceptance rate was 25. 5%).
Language Resources -- A Distributed Database System for Developing Ontological and Lexical Resources in Harmony -- Verb Class Discovery from Rich Syntactic Data -- Growing TreeLex -- Acquisition of Elementary Synonym Relations from Biological Structured Terminology -- A Comparison of Co-occurrence and Similarity Measures as Simulations of Context -- Various Criteria of Collocation Cohesion in Internet: Comparison of Resolving Power -- Why Don’t Romanians Have a Five O’clock Tea, Nor Halloween, But Have a Kind of Valentines Day? -- Best Student Paper Award -- SIGNUM: A Graph Algorithm for Terminology Extraction -- Morphology and Syntax -- Arabic Morphology Parsing Revisited -- A Probabilistic Model for Guessing Base Forms of New Words by Analogy -- Unsupervised and Knowledge-Free Learning of Compound Splits and Periphrases -- German Decompounding in a Difficult Corpus -- Clause Boundary Identification Using Conditional Random Fields -- Semantics and Discourse -- Natural Language as the Basis for Meaning Representation and Inference -- Layer Structures and Conceptual Hierarchies in Semantic Representations for NLP -- Deep Lexical Semantics -- On Ontology Based Abduction  for Text Interpretation -- Analysis of Joint Inference Strategies for the Semantic Role Labeling of Spanish and Catalan -- A Preliminary Study on the Robustness and Generalization of Role Sets for Semantic Role Labeling -- XTM: A Robust Temporal Text Processor -- Invited Paper -- What We Are Talking about and What We Are Saying about It -- Trusting Politicians’ Words (for Persuasive NLP) -- Sense Annotation in the Penn Discourse Treebank -- Word Sense Disambiguation and Named Entity Recognition -- A Semantics-Enhanced Language Model for Unsupervised Word Sense Disambiguation -- Best Paper Award, 1st Place -- Discovering Word Senses from Text Using Random Indexing -- Domain Information for Fine-Grained Person Name Categorization -- Language Independent First and Last Name Identification in Person Names -- Mixing Statistical and Symbolic Approaches for Chemical Names Recognition -- Anaphora and Co-reference -- Portuguese Pronoun Resolution: Resources and Evaluation -- Semantic and Syntactic Features for Dutch Coreference Resolution -- Machine Translation and Parallel Corpora -- Stat-XFER: A General Search-Based Syntax-Driven Framework for Machine Translation -- Invited Paper -- Statistical Machine Translation into a Morphologically Complex Language -- Translation Paraphrases in Phrase-Based Machine Translation -- n-Best Reranking for the Efficient Integration of Word Sense Disambiguation and Statistical Machine Translation -- Learning Finite State Transducers Using Bilingual Phrases -- Learning Spanish-Galician Translation Equivalents Using a Comparable Corpus and a Bilingual Dictionary -- Context-Based Sentence Alignment in Parallel Corpora -- Bilingual Segmentation for Alignment and Translation -- Dynamic Translation Memory: Using Statistical Machine Translation to Improve Translation Memory Fuzzy Matches -- Identification of Transliterated Foreign Words in Hebrew Script -- Natural Language Generation -- Innovative Approach for Engineering NLG Systems: The Content Determination Case Study -- Speech Recognition -- Comparison of Different Modeling Units for Language Model Adaptation for Inflected Languages -- Information Retrieval and Question Answering -- Word Distribution Analysis for Relevance Ranking and Query Expansion -- Hybrid Method for Personalized Search in Scientific Digital Libraries -- Alignment-Based Expansion of Textual Database Fields -- Detecting Expected Answer Relations through Textual Entailment -- Improving Question Answering by Combining Multiple Systems Via Answer Validation -- Text Classification -- Evaluation of Internal Validity Measures in Short-Text Corpora -- Text Summarization -- Arabic/English Multi-document Summarization with CLASSY—The Past and the Future -- Best Paper Award, 3rd Place -- Lexical Cohesion Based Topic Modeling for Summarization -- Terms Derived from Frequent Sequences for Extractive Text Summarization -- Spell Checking and Authoring Aid -- Real-Word Spelling Correction with Trigrams: A Reconsideration of the Mays, Damerau, and Mercer Model -- Best Paper Award, 2nd Place -- Non-interactive OCR Post-correction for Giga-Scale Digitization Projects -- Linguistic Support for Revising and Editing -- The Role of PP Attachment in Preposition Generation -- EFL Learner Reading Time Model for Evaluating Reading Proficiency.
Keywords: Information storage and retrieval; Artificial intelligence; Natural language processing (Computer science).; Mathematical logic; Information Storage and Retrieval; Artificial Intelligence; Natural Language Processing (NLP).; Mathematical Logic and Formal Languages; Natural Language Processing (NLP).